Inovasi Kebijakan Sosial di Tingkat Lokal: Kapasitas Kelembagaan Panglima Laot dalam Pelaksanaan Program Bantuan Asuransi bagi Nelayan - Marini Kristina Situmeang; Hendrie Adji Kusworo (Department of Social Development and Welfare, Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2020)
This article aims to develop an understanding the innovative institutional capacity by taking example from the empirical case pointing out of how the Panglima Laot institution plays its role as a distributor of insurance programs for fishermen. Through a series of qualitative research, this article succed to find that the Panglima Laot's institutional capacity can be categorized in quadrant II since Panglima Laot had already solid formations and functions. Nevetheless in the case of channeling, the function has not perform well. The argument is proven by the fact proving that there are still many fishermen in Lampulo village who are not yet registered as members of the insurance recipient, as well as the number of regularly fishermen who do not yet have a fisherman membership card. It can be concluded that the work of self-service organizations in this case still requires motivation from those who are in institutional externalities.